1997
DOI: 10.1080/15428119791012397
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Disorders, Skin Complaints, and Low-Back Trouble Among Tannery Workers in Kanpur, India

Abstract: In a cross-sectional survey health complaints among 418 laborers in 15 Indian tanneries were studied. Low-back pain (61%), asthma (38%), dermatitis (23%), and chronic bronchitis (14%) were the most frequently reported complaints in the 12 months prior to the survey. In general, beamhouse workers reported the highest prevalence but only chronic low-back pain was significantly elevated compared with workers in the finishing departments. When using individual exposure estimates, clear associations were presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 13 publications
0
15
1
Order By: Relevance
“…The point-prevalence in our study was lower than the reported point-prevalence of the 23% in a cross-sectional survey among 485 tannery workers in India (Ory et al 1997) and 26% in Korean tannery workers (Lee et al 1991). Lee et al (1991) performed a dermatological examination in 310 tannery workers with a prevalence of contact dermatitis of 26.4%.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…The point-prevalence in our study was lower than the reported point-prevalence of the 23% in a cross-sectional survey among 485 tannery workers in India (Ory et al 1997) and 26% in Korean tannery workers (Lee et al 1991). Lee et al (1991) performed a dermatological examination in 310 tannery workers with a prevalence of contact dermatitis of 26.4%.…”
Section: Discussioncontrasting
confidence: 85%
“…The wide range of reported prevalence figures for OSD among tannery workers in newly industrialized countries (between 2.6 and 26.4%) is probably caused by the differences in the definition of cases, period of screening and data collecting (Kvitko 2001; Rastogi et al 2008; Shukla et al 1991; Ory et al 1997). Differences in the working conditions may also cause the wide range of reported point-prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…LBP is one of the leading public health problems with over 80% of the world population reporting LBP at some point in their life [3]. The prevalence of LBP is high especially in low and middle-income countries [46]. …”
Section: Introductionmentioning
confidence: 99%
“…Nurses in developing countries have a higher incidence of occupation-related back pain due to lack of equipment and designs of work [46]. The intensity of LBP has rarely been taken into consideration in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%
“…There have been reports concerning various health problems among workers in tanneries. In the study carried out by Ory et al (14) the health complaints among 418 labourers in 15 Indian tanneries were tested. Asthma (38%), dermatitis (23%) and chronic bronchitis (14%) were the most frequently reported complaints in the 12 months prior to the survey.…”
Section: Introductionmentioning
confidence: 99%